The Influence of Profitability, Firm Size, and Capital Structure on Firm Value with Managerial Ownership as Moderation Variables (Empirical Study of Basic Material Sector Companies on the IDX in 2019-2021) - Friska Puji Rahayu; Sri Wahyuni; Hadi Pramono; Nur Isna Inayati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The condition of the Covid'19 pandemic resulted in a decrease in firm value. The purpose of this study was to analyze profitability, firm size, and capital structure on firm value with managerial ownership as a moderating variable. The population in this study is the company's basic materials registered on the IDX in 2019-2021, the sampling method is purposive sampling, the sample used was 38 samples with certain criteria, while the method of analysis in this study used MRA multiple regression analysis. The results of this study indicate that profitability does not affect firm value, firm size hurts negative firm value, capital structure has a positive effect on firm value, managerial ownership can moderate profitability, firm size is on firm value, and managerial ownership is not able to moderate capital structure on firm value. This research contributes to the field of financial accounting in the form of insight into the factors that influence firm value during a pandemic.